The nature and human ecology in modern kazakh literature - ORDA, G.; SARSENBAYEVA, ZH; ABILKHAIYROV, N; SULTANGALIYEVA, R; MEKEBAYEVA, L (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The article deals with studies of the interactions between man and nature, specifies certain literary lectures such as poems, proses and/or other drama genres by history matching method, and determines the value of the artistic-aesthetic system of modern national literature. The main compositions on the matter of the heart of XX-XXI centuries were specified by comparative study and show science-based reason how the writer brought up the common problems of humans that awaits attention. RESUMEN El artículo trata sobre los estudios de las interacciones entre el hombre y la naturaleza, especifica ciertas lecturas literarias como poemas, prosas y otros géneros dramáticos por el método de comparación de la historia, y determina el valor del sistema artístico-estético de la literatura nacional moderna. Las principales composiciones sobre la materia del corazón de los siglos ХХ-ХХІ se especificaron mediante un estudio comparativo y se demostró la razón basada en la ciencia de cómo el escritor planteó los problemas comunes de los humanos que esperan atención.